Perencanaan Geometri Jalur Kereta Api Kecepatan Tinggi Lintas Bandung Cirebon Fase II (Cimalaka-Ligung) KM 33+850 – KM 67+000 - Aghasta, Adya; Yudha, Aldi Wardana (Civil Engineering Collaboration, 2024)
This research delves into the meticulous geometry planning of the High-Speed Railway Track for the Bandung-Cirebon Phase III (Ligung-Tengahtani), spanning KM 67+000 to KM 100+685.72. In pursuit of engineering excellence, the study leverages cutting-edge Autocad Civil 3D, Global Mapper and ArcGIS Student technology and exhaustive field surveys to craft a track alignment that redefines speed and safety standards. The design intricately weaves together horizontal and vertical curves, superelevation, and gradient, ensuring the railway not only conquers the challenging terrain but also elevates the operational efficiency to unprecedented levels. This work sets a new benchmark in high-speed rail infrastructure, delivering a masterfully engineered blueprint that promises to revolutionize connectivity and economic growth in Indonesia.